To Boost Students Speaking Skill through Mobile Augmented Reality - Islam, Syaiful; Muali, Chusnul (International Journal of English Education and Linguistics (IJoEEL), 2023)
There has recently been a spike in student enthusiasm in using technology to engage in their study. Augmented reality is one of the technologies that has been determined to be acceptable for usage in educational settings such as science, mathematics, and engineering. As a result, this study looked into the usefulness of employing mobile augmented reality (MAR) to improve students' speaking skills. This study employed a quasi-experimental approach with two groups: control and experimental. They are conducting MAR and traditional instructional methods teaching and learning sessions. According to the findings of this study, students in the experimental group demonstrated considerably higher levels of speaking skills than those in the control group following teaching and learning. Furthermore, this study discovered that MAR can help to highlight student-centered learning, stimulate student interest and curiosity, improve student cognitive, emotional, and psychomotor processes, and increase student involvement in the information-seeking process. It is recommended that educators employ MAR in their teaching and learning since it has effectively improved students' speaking skills and encouraged a better grasp of knowledge